Pengaruh Label Halal, Kebutuhan, Dan Literasi Keuangan Terhadap Keputusan Pembelian Kosmetik Pada Mahasiswa Di Perguruan Tinggi Kabupaten Sorong - Atina Melinda.A; andi hasrun; Vantri Pieter Kelelufna (At-Thariqah: Jurnal Ekonomi, 2025)
This study aims to determine the influence of halal labels, needs, and financial literacy on cosmetic purchasing decisions among college students in Sorong Regency. The study used a quantitative method with a descriptive approach. The study sample consisted of 95 respondents, namely active college students at universities in Sorong Regency who regularly use cosmetics. Data were collected through a Google Form and analyzed using multiple linear regression. The results showed that halal labels did not influence consumer purchasing decisions for cosmetic products, with a calculated t-value < t-table (0.224 < 1.986). Similarly, needs did not influence purchasing decisions (calculated t-value < t-table: 0.267 < 1.986). Conversely, financial literacy significantly influenced consumer purchasing decisions for cosmetic products, as evidenced by a calculated t-value > t-table (7.680 < 1.986).